Patrimônio geomorfológico da vertente seca do Maciço de Uruburetama e entorno, Ceará, Nordeste do Brasil - Islane Pinto de Carvalho; Abner Monteiro Nunes Cordeiro; Frederico de Holanda Bastos (Confins)
The Uruburetama Massif, located in the north Ceará state, Brazil, is one of the largest residual granitic reliefs in the state context. In view of its geological and geomorphological complexity, this massif exhibits macro and micro granitic forms, which constitute a potential geomorphological heritage. Thus, this work aimed to identify granitic geoforms with relevant scientific value in the context of this massif, in view of their didactic sampling associated with the taxonomy of granitic reliefs and also in terms of the interpretation of fundamental morphogenetic and paleoclimatic processes for understanding landscapes of the Brazilian semiarid region. The methodological procedures employed (bibliographic review, fieldwork and cartographic interpretation) made it possible to inventory 14 geomorphosites in the dry slope of the Massif of Uruburetama covering the municipalities of Irauçuba, Itapipoca and Itapajé.